WILLIAM HAZLITT, OBSESSIVE LOVE, AND LIBER AMORIS. (July 2017) - TROSMAN, HARRY
Abstract : William Hazlitt, a distinguished literary figure of the early nineteenth century and a forerunner of psychoanalytic insights, had a keen awareness of the impact of the imagination on assessing works of art. At forty‐two, he became hopelessly involved in an obsessive love affair with a nineteen‐year‐old woman and could not extricate himself from the relationship. The affair followed the death of his father, a powerful influence on his life. Factors in his obsessive love included finding an object of idealization subject to his imaginative creation and narcissistically reexperiencing himself about to begin a new life.